The Elementary Students' Skills In Predicting And Understanding Concept Using Predict-Observe-Explain (Poe) Strategy In Zoom-Meeting Learning - Putri, Sheryl Mutiara; Sopandi, Wahyu; Sujana, Atep; Sukardi, Rendi Restiana (Universitas Pendidikan Indonesia, 2021)
As an impact of the Covid-19 pandemic, learning is now carried out online. The purpose of this study was to describe the effectiveness of the Predict-observe-explain (POE) strategy in improving elementary students' skills in predicting and understanding the science concept assisted by zoom meeting. This study used a pre-experimental method with a one-group interpretation-posttest design. The subjects of this study consisted of 20 students of grade V (five) odd semester of a private elementary school in city of Bandung. Research instrument in the form of pretest, posttest, and predicting skills were given to students using a two-level diagnostic test. Data collection is done using google form. The results showed that the predict-observe-explain (POE) strategy, through demonstration video assisted by zoom meeting could help students improve their predicting skills and conceptual understanding.